A note on observations of cetaceans in the Indian Ocean Sanctuary, Australia to Israel, April 1995 - Eyre, Elizabeth J.; Frizell, John (J. Cetacean Res. Manage., 2023)
A forty-day voyage from Hobart (Australia) to Haifa (Israel) included a visual and acoustic census for cetaceans in the Indian Ocean Sanctuary. One hundred and sixty-three sightings were made, 156 occurring within the Sanctuary. Twelve species were identified. Sperm whales (Physeter macrocephalus) were encountered most frequently (51% of identified encounters), whilst spinner dolphins (Stenella longirostris) were numerically dominant. Other species identified included bottlenose dolphins (Tursiops spp.), short-beaked common dolphin (Delphinus delphis), pan-tropical spotted dolphin (Stenella attenuata), rough-toothed dolphin (Steno bredanensis), Risso’s dolphin (Grampus griseus), killer whale (Orcinus orca), short-finned pilot whale (Globicephala macrorhynchus), false killer whale (Pseudorca crassidens), Bryde’s whale (Balaenoptera edeni) and Cuvier’s beaked whale (Ziphius cavirostris). The most sightings occurred WNW of the Seychelles, east of Somalia, and in the Gulf of Aden and Red Sea. Half of the sperm whale sightings were to the east of Ras Hafun (Somalia), and included adults, subadults and at least one calf. Thirteen hours were spent listening for cetaceans using a towed array whilst the ship was underway. Cetaceans were detected at 78% of the listening stations, with a possible four species recorded (sperm whale, spinner dolphin, pilot whale, bottlenose dolphin). The survey shows the value of platforms of opportunity for studying the pelagic communities of cetaceans in the Indian Ocean Sanctuary. It highlights the need for further research in the northwestern sector where anthropogenic threats are varied and increasing.